2003
DOI: 10.1023/a:1025476910771
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The preincubation of oocytes for at least 2.5 h is beneficial to both IVF and ICSI outcomes by increasing the nuclear maturity of oocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…It has been reported that a preincubation period between oocyte retrieval and injection in ICSI cycles improved the percentage of mature oocytes [5, 6], the fertilization rate [1, 6, 7], and the embryo quality [1, 2]. A long oocyte preincubation (9–11 hours) prior to ICSI is thought to have bad effects on embryo quality [2], probably due to oocyte ageing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that a preincubation period between oocyte retrieval and injection in ICSI cycles improved the percentage of mature oocytes [5, 6], the fertilization rate [1, 6, 7], and the embryo quality [1, 2]. A long oocyte preincubation (9–11 hours) prior to ICSI is thought to have bad effects on embryo quality [2], probably due to oocyte ageing.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been shown that incubation of oocytes for 2–6 h prior to IVF ( In Vitro Fertilization) improves fertilization and pregnancy rates [ 9 12 ], there are some conflicting results regarding the timing of ICSI. It has been reported that a preincubation period between oocyte retrieval and injection in ICSI cycles improved the percentage of mature oocytes [ 5 , 6 ], the fertilization rate [ 1 , 6 , 7 ], and the embryo quality [ 1 , 2 ]. A long oocyte preincubation (9–11 hours) prior to ICSI is thought to have bad effects on embryo quality [ 2 ], probably due to oocyte ageing.…”
Section: Introductionmentioning
confidence: 99%
“…Although being of paramount clinical importance, the timing of fertilization remains a subject of controversy. Clinical data support the notion that a pre-incubation interval between oocyte retrieval and ICSI improves the outcome of IVF treatment [ 12 , 14 , 32 , 33 ]. However, other studies recommended limiting the cultivation period to prevent post-ovulatory aging of the oocyte [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 79%
“…However, immature oocytes, which spontaneously extruded PB in vitro, have been successfully used in fertility treatment [ 6 10 ]. Cumulative evidence suggests that the developmental potential of late-maturing oocytes could be better exploited if the timing of ICSI is adjusted to their developmental stage [ 2 5 , 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous substantial studies have examined the optimal time for oocyte denuding and ICSI. While it remains controversial, it has been reported that a 2–6 h interval between oocyte retrieval and ICSI can improve oocyte maturation, fertilization, embryo quality and even pregnancy rate [ 26 28 ]. This optimal timing is probably associated with the spindle presence in the oocyte [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%